Mechanistic Study on the Selective Oxidation of Acrolein to Acrylic Acid: Identification of the Rate-Limiting Step via Perdeuterated Acrolein - Knoche, Stefan; Heid, Maurice; Gora, Niklas; Ohlig, Dominik; Drochner, Alfons; Hess, Christian; Etzold, Bastian J.M.; Vogel, Herbert (ChemCatChem, 2019)
Gas phase oxidation of acrolein to acrylic acid on hydrothermally prepared Mo/V/W mixed oxides was investigated by isotopic labeling of acrolein. In this context, perdeuterated acrolein was synthesized for the first time and subsequently used for mechanistic studies. A clear kinetic isotopic effect (KIE) is observed referring to the α-hydrogen-abstraction as the rate-determining step in the selective acrolein oxidation. Furthermore, no change in the selectivity patterns is observed due to the perdeuteration, which confirms that the α-hydrogen-abstraction also acts as the rate-limiting step in the total oxidation of acrolein. Based on these KIE studies combined with additional experiments including D2O-SSITKA and temperature-programmed desorption, a detailed reaction mechanism for acrolein oxidation is proposed.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Acrylic acid; Deuteration; Isotopic labeling; Kinetic isotopic effect; Mo-V-oxides